The ongoing debate on NBTs and possible roads for the future - Romeo Lironcurti, Simona; Demaria, Federica; Quarto, Angelo; Solazzo, Roberto (Frontiers in Political Science, 2024)
There are marked differences in the approaches that regulate genetically modified (GM) products and the new breeding techniques (NBTs) in the European Union (EU) and in other areas of the world. Through the review of regulations and ongoing discussions, we show that the world can be divided in two groups based on the discrepancies in the approach of the country's regulations. On the one hand, Europe, with the main countries of Asia and Africa, regulates New Breeding Techniques as a genetically modified organism. On the other, a group of countries mainly located in the American continent, together with Australia, adopted a case-by-case approach, and are generally at a more advanced stage in the implementation of these new techniques. The paper aims to evaluate the possible evolution in the countries' regulations on the use of NBTs in the next years. The division between Western and Eastern countries of the world is confirmed, with some interesting movements in some regions. Greater uniformity among national regulations would be desirable to promote the implementation of biotechnologies in agriculture. The main research findings are that most EU Member States have taken a conservative position, whereas the Eastern group is more advanced and this could be a driving force for some regions toward acceptance of these technologies in the coming years.